Detached eclipsing binaries in compact hierarchical triples: triple-lined systems BD+442258 and KIC 06525196. Issue 2 (6th March 2023) - Moharana, Ayush; Hełminiak, K G; Marcadon, F; Pawar, T; Konacki, M; Ukita, N; Kambe, E; Maehara, H
ABSTRACT: Compact hierarchical triples (CHTs) are systems with the tertiary star orbiting the inner binary in an orbit shorter than 1000 d. CHT with an eclipsing binary as its inner binary can help us extract a multitude of information about all three stars in the system. In this study, we use independent observational techniques to estimate the orbital, stellar, and atmospheric parameters of two triple-lined CHT: BD+44 2258 and KIC 06525196. We find that the masses of stars in BD+44 2258 are $1.011± 0.029$, $0.941± 0.033$, and $0.907± 0.065 \, {\rm M}_{\odot }$ while in KIC 06525196 the estimated masses are $1.0351± 0.0055$, $0.9712± 0.0039 $, and $0.777± 0.012 \, {\rm M}_{\odot }$ . Using spectral disentangling, we obtained individual spectra of all the stars and combined it with light-curve modelling to obtain radii, metallicities, and temperatures. Using stellar evolution models from mesa, we constrain the log(age) of BD+44 2258 to be 9.89 and 9.49 for KIC 06525196. Two stars in BD+44 2258 are found to be sub-giants while all three stars in KIC 06525196 are main-sequence stars. We constrain the mutual inclinations to certain angles for BD+44 2258 and KIC 06525196 using numerical integration. Integrating with tidal interaction schemes and stellar evolution models, we find that KIC 06525196 is a stable system. But the inner binary of BD+44 2258 merges within 550 Myr. The time of this merger is affected by the orientation of the tertiary, even rushing the collapse by ∼100 Myr when the mutual inclination is close to 90 ○ .